Conversation Analysis of Repair in Variety Actors on Actors Between Saoirse Ronan and Kristen Wiig (2017) - Ganjar Qurrotul 'Aini (Metaphor, 2022)
The study aimed to identify the types of repair and repair operations used by Saoirse Ronan and Kristen Wiig in Variety Actors On Actors. The researcher used a theory of types of repair by Schegloff et al. in Liddicoat (2007) and a theory of repair operations by Schegloff in Conversational Repair and Human Understanding (2013). This type of research was qualitative method. The researcher used an approach qualitative descriptive to describe the types of repair and repair operation that included in conversation between Saoirse Ronan and Kristen Wiig in Variety Actors On Actors as the objective of the research. The result of this study showed that there are three types of repair occurred in the conversation. There are 36 occurrences of self-initiated self-repair, 2 occurrences of self-initiated other-repair, and I occurrence of other-initiated self-repair. The result of this study also found that there are six repair operations occurred in the conversation. There are 3 occurrences inserting, 1 occurrence of deleting, 5 occurrences parenthesizing, 20 occurrences aborting, 3 occurrences recycling, and 4 occurrences reformatting.